Diversity of Ploidy Level and Morphology of Stevia rebaudiana Bertoni Induced by Colchicine - Ridhawati, Aprilia; Saptadi, Darmawan; Waluyo, Budi; Kuswanto, Kuswanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
The constraints in the generative propagation of stevia include a limited supply of fertile seeds, suboptimal germination rates, and significant phenotypic variability, all of which hinder conventional breeding efforts. Vegetative propagation causes genetic uniformity but limits genetic diversity. Another method for breeding stevia is by inducing polyploidy with colchicine. The main goals of polyploidy induction are to enhance diversity, improve agronomic traits, and achieve ploidy higher than diploid. This study evaluated the ploidy levels and morphological responses of two accessions (SR16 and SR17) to five colchicine doses (0.05, 0.1, 0.15, and 0.2%) and three soaking periods (8, 16, and 24 hours). The accession SR16 showed the best response to 0.1% colchicine for 8 hours and to 0.15% for 12 hours, causing ploidy levels to shift from diploid to tetraploid and mixoploid. SR17, on the other hand, needed higher concentrations and longer immersion times (0.2% for 12 hours) to show the same range of variability. The changes in shape depended on the genotype. SR16 needed low to moderate levels of immersion for short periods, while SR17 needed high levels for long periods. These results endorse the utilization of polyploidy induction techniques in stevia breeding to enhance production and sweetness quality.